IMPLEMENTATION OF THE YANBU'A METHOD TO IMPROVE STUDENTS' LEARNING OUTCOMES IN READING THE QUR'AN IN ISLAMIC BOARDING SCHOOLS - Solehah, Imbrotus; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and understand the implementation of the Yanbu'a method to improve student's learning outcomes in reading the Koran in Islamic boarding schools. This research uses a descriptive qualitative approach, a case study type. The data collection technique was carried out through observation, documentation, and interviews to determine the learning outcomes of students in reading the Koran using the Yanbu'a method. Data analysis starts with data presentation and data reduction and ends with drawing conclusions. The results of this research show that the implementation of the yanbu'a method is easy to learn and remember and can produce a fluent and start reading. This yanbu'a method uses a multisensory approach, namely using sight, hearing, and body movements in the learning process. This makes learning more effective and enjoyable. The Yanbu'a method also uses a gradual approach, starting from introducing the hijaiyah letters, then connecting the letters, until finally reading the Al-Qur'an fluently.